Peran Media Pembelajaran APE “Puzzle Tempel Huruf” Terhadap Kemampuan Membaca Siswa Kelas 1 SD Negeri Semin III - Triwinarti, Anik; Henu Cahyani , Berliana; Sudigdo, Anang (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The Indonesian language is the official language used in Indonesia. Good and proper reading skills in Indonesian are crucial for students, especially first-grade elementary school students. Reading is a fundamental skill that students must master to access information from various sources and understand multiple subjects well. APE